Atividade carrapaticida, repelente e anti-helmíntica de terpenos encapsulados e associação de um terpeno com carrapaticida sintético sobre Rhipicephalus microplus, Haemonchus contortus e Caenorhabditis elegans - LIMA, Aldilene da Silva (2018)
Rhipicephalus microplus and Haemonchus contortus are the main problem of economic importance to for livestock production systems. The parasite’s control has been selected resistant tick and nematodes populations. Terpene can be an alternative for parasites control, due to low residual effect and toxicity, however this compound is highly volatile and is need formulations to decrease volatility. The aim of the present study was to evaluate the acaricide, repellent and antihelminthic efficacy of terpenes encapsulated with yeast cell wall of Sacharomyces cerevisiae on R. microplus and H. contortus. Analysis of scanning electron microscopy, and Fourrier Transformed Spectrometry were performed to verify encapsulation. The tick efficacy of the carvacrol encapsulated and non-encapsulated and the efficacy after volatility effect of the compounds was measured using the larval immersion test in susceptible and resistant strains of R. microplus. The repellent effect of carvacrol encapsulated and non-encapsulated was measured using repellency test. Antihelminthic activity was measured using larval exsheathment inhibition, Egg hatching and adult motile assay, used free-living nematode Caenorhabditis elegans. The results of scanning electron microscopy, and Fourrier Transformed Spectrometry showed that the terpenes were encapsulated by yeast cell wall. The vibrational bands showed similar between the analyzed samples, characteristic bands of the chemical structure of the compounds used. The mean particle size of the carvacrol encapsulated was 2-fold greater than the yeast cell wall. The carvacrol encapsulated exhibited higher efficacy than the carvacrol non-encapsulated until 60 h post initial of volatility test. The carvacrol encapsulated exhibited higher repellent efficacy, with a low repellent concentration all times, while, the carvacrol nonencapsulated ranging CR50 from 0.13 a 0.27mg/cm2 at 1 to 6 h post treatment. The encapsulated compound showed acaricide, repellent and anthelminthic activity can be a potential for new delivery systems of volatile and hydrophobic compounds.